Using a competency-based approach in the training of future foreign language teachers (Pedagogy of Higher and Secondary Education, 2021)
The article determines the essence of competence approach during foreign languages’ study at the institute of higher education, exposes a foreign language teacher’s key competences, considers the aims of foreign languages’ study at the aspect of the mentioned approach.
Keywords: competence approach; competence; communicative competence; didactic competence; the aims of study